Expression of cytokeratin and vimentin in villi of the chorion with anteintranatal fetal death on the background of complicated pregnancy - Zats, Olha; Sherstiuk, Sergey; Sydorenko, Ruslan; Sherstiuk, Liudmila; Panov, Stanislav (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. Approximately 3–10 % of all pregnancies are complicated by premature rupture of membranes (PRM). Pregnancy in the presence of preeclampsia, gestational iron deficiency anemia, and acute chorioamnionitis increases the risk of PRM development. These complications of pregnancy are etiologically related to the factors causing PRM, the most important of which are oxidative stress with the subsequent development of sterile inflammation, droplet bleeding with the formation of a posterior placental hematoma, and inflammation of the placenta and fetal membranes. Aim. To determine the expression of cytokeratin and vimentin in chorionic villi with ante-intranatal death of fetuses against the background of complicated pregnancy. Materials and methods. The first studied group included 8 cases of PEN; in the second group – 8 PED observations; in the third group – 8 cases of AN; on the fourth – 8 cases of AD; in the fifth – 10 observations of KHAN; in the sixth – 16 cases of HAD. For the immunohistochemical (IGH) study, an indirect immunoperoxidase method was used using MCA for cytokeratin pan (AE-1/AE-3) (DAKO, Denmark) – epithelial cells were identified, and MCA for vimentin (V9) (DAKO, Denmark) - mesenchymal cells were identified cells. Results. In clinical groups with preterm pregnancy, the intensity of the reaction was well expressed in the epithelium of normal villi and unevenly expressed or absent in immature and sclerosed villi. The level of expression of cytokeratin by the epithelium of the villi in these groups was significantly higher compared to the CG group. In the groups with full-term pregnancy, the intensity of the IHC reaction was weakly expressed in the epithelium of normal villi and weakly expressed or absent in immature and sclerosed villi. The level of expression of cytokeratin by the epithelium of the villi in these groups was significantly lower compared to both the CG group and premature pregnancy in the case of similar pathology. In clinical groups with full-term pregnancy, the expression level of vimentin in mesenchymal cells of villi increased significantly compared to clinical groups with similar pathology of prematurity and compared to the CG group. Conclusions. In the villi of the chorion, some cells of the syncytial epithelium are transformed into mesenchymal cells with fibroblast-like properties, which can be confirmed by the appearance of vimentin-positive epithelial cells in the syncytiotrophoblast of the villi.